Isolated ventriculomegaly on prenatal ultrasound: What does fetal MRI add?. Issue 2 (2nd March 2015) - Kandula, Tejaswi; Fahey, Michael; Chalmers, Rebecca; Edwards, Andrew; Shekleton, Paul; Teoh, Mark; Clark, Jenni; Goergen, Stacy K.
Abstract Introduction Cerebral ventriculomegaly is one of the most commonly detected fetal anomalies at the midtrimester ultrasound. Current evidence suggests that magnetic resonance imaging (MRI) is indicated when the isolated ventriculomegaly (IVM) on ultrasound is severe (>15 mm), but there is less agreement when IVM is mild or moderate (10–15 mm). The current study aimed to determine the frequency and nature of additional findings on MRI in IVM and their relationship to the severity of VM and gestational age. Methods Data were gathered prospectively from all pregnant women with ultrasound‐diagnosed IVM referred for MRI between November 2006 and February 2013. Cases with IVM and no other suspected cranial abnormality on a tertiary ultrasound performed at our institution, at or after 20 weeks gestation, were included. Results Of the 59 fetuses with unilateral or bilateral IVM, additional findings were seen on MRI in 10 cases (17%) and half of these findings were identified in fetuses with mild IVM. Five of 40 (12.5%) fetuses with mild IVM had additional findings and 3/5 (60%) were potentially clinically significant. No additional abnormalities were identified in fetuses less than or equal to 24 weeks gestation with mild or moderate IVM. There was no statistically significant relationship between gestational age and additional findings on MRI in mild IVM. Callosal and septum pellucidum lesions, periventricular abnormalities and malformations of cortical development accounted for all of the significant additional findings. Conclusion This study helps to inform referral of pregnant women with a fetus who has IVM for prenatal MRI.